Pregnancy Outcome in Infertility Patient with Endometriosis Cyst after Laparoscopic Cystectomy - Gunardi, Eka R; Tritama, Duta A; Satria, Luky; Situmorang, Herbert (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To investigate about the rate of pregnancy in womenwho had undergone laparoscopic cystectomy.Methods: This was a retrospective study. Data were taken from themedical records of patients with infertility in Fatmawati Hospital,Jakarta, Indonesia. Data then analyze to know is there anyassociation between age, infertility duration, bilaterality of the cyst,tubal patensy, r-AFS stage with pregnancy rate.Results: A total of 64 subjects were recruited in this study. Therewere 23 subjects (35.9%) that got pregnant within one year afterundergoing laparoscopic procedure. Those who were 35 years oldor less had a greater chance to get pregnant (p = 0.01, OR = 6.75),duration of infertility  3 years had a greater chance to getpregnant with OR = 3.2 and p value = 0.032, r-AFS stage II and IIIhad a greater chance to get pregnant to with (p = 0.04, OR = 3.25and 4.25).Conclusion: The pregnancy rate after laparoscopic procedure is35.9% in this study. There are correlation between age, durationof infertility, and r-AFS staging with pregnancy rate.[Indones J Obstet Gynecol 2018; 6-1: 34-38]Keywords: endometriosis, infertility, laparoscopy, pregnancy